On Thermal Expansion and Density of CGI and SGI Cast Irons - Taishi Matsushita; Ehsan Ghassemali; Albano Gómez Saro; Lennart Elmquist; Anders E. W. Jarfors (Metals, 2015)
The thermal expansion and density of Compacted Graphite Iron (CGI) and Spheroidal Graphite Iron (SGI) were measured in the temperature range of 25–500 °C using push-rod type dilatometer. The coefficient of the thermal expansion (CTE) of cast iron can be expressed by the following equation: CTE = 1.38 × 10−5 + 5.38 × 10−8 N − 5.85 × 10−7 G + 1.85 × 10−8 T − 2.41 × 10−6 RP/F − 1.28 × 10−8 NG − 2.97 × 10−7 GRP/F + 4.65 × 10−9 TRP/F + 1.08 × 10−7 G2 − 4.80 × 10−11 T2 (N: Nodularity, G: Area fraction of graphite (%), T: Temperature (°C), RP/F: Pearlite/Ferrite ratio in the matrix).